An improved method for separating styrene-butadiene-styrene triblock copolymer (SBS) and bitumen matrix from SBS modified bitumen. (15th February 2021) - Yang, Xue; Zhang, Henglong; Chen, Zihao; Shi, Caijun
Highlights: A novel method for separating SBS from SBS modified bitumen was developed. The aging susceptibility of bitumen matrix in SBSMB is lower than that of pure bitumen. The content of SBS in SBSMB can be determined by the proposed separation method. Abstract: Developing a reliable method for separating styrene-butadiene-styrene triblock copolymer (SBS) modifier and bitumen matrix is not only beneficial to further revealing the aging mechanism of SBS modified bitumen (SBSMB) but also can be used to determine the SBS content in SBSMB. Consequently, two separation methods were compared based on solubility differences of SBS, asphaltene and maltene in specific chemical agents, and evaluated by rheological, chemical and morphological analyses. In addition, the application of proposed separation method to SBSMB aging research and SBS content determination was also conducted. The results show that the separation method that first separates asphaltene from SBSMB, and then separates SBS and maltene in residues can successfully separate SBS and bitumen matrix. No new bulk phase is apparent in bitumen after separation processes, and the separation processes of proposed method have few influences on complex modulus of binder while having significant impacts on phase angle of binder. By comparing pure bitumen and separated bitumen matrix from SBSMB, it can be found that the aging susceptibility of bitumen matrix in SBSMB is lower than that of pure bitumen. Moreover, the content of SBS in SBSMB can also be accurately determined by the proposed separation method, which can contribute to quality control of SBSMB products.